Estrategias administrativas y financieras para las empresas de producción de lácteos de la Ciudad de Gonzanamá - Briceño Castillo, Carmen del Rocio (2023)
The implementation of strategies in dairy production companies is crucial because it allows them to have an action plan that helps improving performance across all areas, ensuring the profitability of the business, production efficiency, and product quality. Therefore, the purpose of this research was to develop administrative and financial strategies for dairy- producing companies in the City of Gonzanamá, aiming to propose plans that guide organizations toward growth, development, and sustainability in the market. This academic paper used a qualitative and quantitative approach with an exploratory, descriptive, and explanatory level. The analysis unit consisted of three companies in the City of Gonzanamá, and the data collection instrument was a survey. The diagnostic results revealed that there are more weaknesses than strengths in the organizations, both in the administrative and financial processes. Hence, a strategic plan was developed, with four strategies directed towards the administrative domain and five established for financial management. All proposed strategic plans aimed to enable companies to plan and control their processes to minimize actual and future risks. In conclusion, administrative and financial strategies are useful for companies as they describe potential competitive advantages to keep market presence, ensure efficiency and control in various areas, and contribute to the development of administrative processes that secure the economic and financial sustainability of organizations.